ANALYSIS OF THE PSYCHOLOGICAL CLIMATE IN HEALTHCARE INSTITUTIONS (USING THE EXAMPLE OF HEALTHCARE INSTITUTIONS IN MYKOLAIV) - Anastasia Shulga; Roman Romazanov; Iryna Savchuk (Публічне управління та регіональний розвиток)
The article analyzes the psychological climate in the collectives of healthcare institutions under modern conditions (on the example of healthcare institutions in the city of Mykolaiv). At the beginning of the study, the content of the key concepts – «collective», «psychological climate» is disclosed. The characteristic features inherent in the psychological climate in the collective are outlined. The types of psychological climate in the collective are described and their subjective and objective signs, which determine their corresponding indicators, are indicated. The main part of the article is devoted to the analysis of the psychological climate in the collectives of healthcare institutions in Mykolaiv based on the results of an anonymous survey of employees of the specified institutions. More than two hundred respondents of different gender and age groups, who have different lengths of work experience and hold different positions in the healthcare institutions, are taken part in the sociological research. As a result of the conducted questionnaire, the type of psychological climate was determined, which to a greater extent is characteristic of the collectives of healthcare institutions in Mykolaiv. Separately, the employees of these institutions are asked several questions related to moral-ethical and work points, and a scale from 1 to 5 is offered, based on which it is necessary to answer. On the basis of the obtained data, it is summarized that most of the respondents feel an atmosphere of mutual understanding and mutual assistance; in the collectives, it is not customary to criticize and communicate in a rude or offensive manner. At the same time, it is found that negative rumors, false information or discussion of employees' personal lives are being spread in some collectives. In addition, there are rare cases when management unjustifiably favored individual employees. At the end of the article, it is concluded that, according to the results of the questionnaire, a favorable psychological climate prevails in the collectives of healthcare institutions in Mykolaiv. Ways to strengthen such a climate, taking into account the current socio-economic situation and the full-scale war in Ukraine are proposed.